Determination and thermodynamic modeling of solid–liquid phase equilibrium for 3, 5-dichloroaniline in pure solvents and ternary 3, 5-dichloroaniline + 1, 3, 5-trichlorobenzene + toluene system. (July 2016) - Li, Rongrong; Du, Cunbin; Meng, Long; Han, Shuo; Wang, Jian; Zhao, Hongkun
Graphical abstract: Highlights: Solubility of 3, 5-dichloroaniline in seven organic solvents were determined. Solid–liquid phase equilibrium for ternary system was measured. The binary and ternary phase diagrams were constructed. The phase diagrams were correlated with thermodynamic models. Abstract: The solid–liquid phase equilibrium data for 3, 5-dichloroaniline in n -propanol, isopropanol, n -butanol, isobutanol, toluene, ethyl acetate and acetone at (283.15 to 308.15) K were determined experimentally by gas chromatography under 101.3 kPa. The solubility of 3, 5-dichloroaniline in these solvents decreased according to the following order: ethyl acetate > (acetone, toluene) for the solvents of ethyl acetate, acetone, and toluene; and for the other solvents, (isopropanol, n -butanol) >  n -propanol > isobutanol. According to the solubility of 3, 5-dichloroaniline in pure solvents, the solid–liquid phase equilibrium for the ternary mixture of 3, 5-dichloroaniline + 1, 3, 5-trichlorobenzene + toluene were measured by using an isothermal saturation method at three temperatures of 283.15, 293.15, and 303.15 K under 101.3 kPa, and the corresponding isothermal phase diagrams were constructed. Two pure solids were formed in the ternary system at a fixed temperature, which were pure 3, 5-dichloroaniline and pure 1, 3, 5-trichlorobenzene and were identified by Schreinemakers' method of wet residue. The temperature dependence of 3, 5-dichloroaniline solubility in pure solvents was correlated by the modified Apelblat equation, λ h equation, Wilson model and NRTL model; and the ternary solid–liquid phase equilibrium of 3, 5-dichloroaniline + 1, 3, 5-trichlorobenzene + toluene were described by the Wilson model and NRTL model. Results showed that calculated solubility values with these models agreed well with the experimental ones for the studied binary and ternary systems. The solid–liquid equilibrium and the thermodynamic models for the binary and ternary systems can offer the foundation for purification of 3, 5-dichloroaniline from its mixture.